2011
DOI: 10.1016/j.foodchem.2010.12.157
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a UHPLC-FLD method for the simultaneous quantification of aflatoxins, ochratoxin A and zearalenone in barley

Abstract: Limits of detection were 340 ng kg -1 for ZEA, 13 ng kg -1 for OTA and varied from 0.5 to 15 ng kg -1 for aflatoxins. Recovery percentages were between 78.2 and 109.2%. After being validated, the method has been successfully applied to 20 barley samples cultivated in a region of northern Spain (Navarra).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…Then the samples were extracted and analyzed using the method described above. Recovery values for barley and malt were comparable to those given in the literature for barley (Ibáñez-Vea at al., 2011) and other cereals, such as maize (Lattanzio et al, 2007;Rahmani, Jinap, Soleimany, Khatib, & Tan, 2011). Recovery for beer was also in compliance with the published data (Nakajima et al, 1999;Ventura et al, 2006;Zachariasova et al, 2010).…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Then the samples were extracted and analyzed using the method described above. Recovery values for barley and malt were comparable to those given in the literature for barley (Ibáñez-Vea at al., 2011) and other cereals, such as maize (Lattanzio et al, 2007;Rahmani, Jinap, Soleimany, Khatib, & Tan, 2011). Recovery for beer was also in compliance with the published data (Nakajima et al, 1999;Ventura et al, 2006;Zachariasova et al, 2010).…”
Section: Methodssupporting
confidence: 84%
“…The most commonly used test for screening of aflatoxins in food is the commercially available set ELISA (e. g. Ghali, Hmaissia-khlifa, Ghorbel, Maaroufi, & Hedili, 2008), highperformance liquid chromatography with fluorescent (Jaimez et al, 2000) or mass -spectrometric detection is employed for more accurate determination. Currently, multiresidual methods for the analysis of more mycotoxins from one food matrix have been developed (e. g. Berthiller, Sulyok, Krska, & Schuhmacher, 2007;Ibáñez-Vea et al, 2011;Ventura et al, 2006;Zachariasova et al, 2010). The advantage is a lower price of the analysis and detection of simultaneous occurrence of more toxins.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that eight samples (19%) were contaminated with aflatoxins, ranging from 6.5 to 101.9 ng g −1 . Ibáñez-Vea et al (2011) evaluated AFG2, AFG1 and ZEA mycotoxins in 20 barley samples. All of the samples analyzed presented levels of AFB1 above its LOD, but only 5 (25%) presented quantifiable levels (>LOQ), with 0.173 μg kg −1 and 0.185 μg kg −1 being the mean of the positive values and the maximum level found, respectively.…”
Section: Factors Promoting Contamination In Aflatoxins and Occurrencementioning
confidence: 99%
“…Analysis of mycotoxins in foods is often based on GC (3)(4)(5) and HPLC in combination with diodearray (6,7), flurorescence (8,9), and MS/MS (10,11) detectors. Most recently developed methods use a commercial immunoaffinity column for clean-up following solvent extraction.…”
Section: Introductionmentioning
confidence: 99%